Integrated reporting stimulates strategic communication of corporate social responsibility?: A marketing perspective analysis based on Maignan, Ferrell and Ferrells stakeholder model of corporate social responsibility in marketing - Baptista,Nuno (2018)
Integrated reporting brings the promise of a new approach to corporate reporting based on integrated thinking, long-term focus, a broader view of value creation and a better articulation of organizations strategy and business models and further integration of corporate social responsibility and sustainability in business. Despite the potential of integrated reporting to drastically change the way corporate social responsibility is currently reported, marketing scholars focusing on ethics and social responsibility seem to be alienated from the discussion occurring in academia about integrated reporting. In this article we evaluate if integrated reports, as conceptualized by the International Integrated Reporting Council, may be used as a relevant source of information to operationalize Maignan, Ferrell and Ferrells stakeholder model of corporate social responsibility. We conclude that integrated reports present some important limitations, mostly related with being exclusively focused on the information needs of investors and not requiring companies to report on the full impact of their activities on other stakeholders. This study contributes to this special issue dedicated to the topic of strategic communication by framing the potential contribution of integrated reporting to strategic communication of corporate social responsibility.